Deciphering modulation of anti-inflammatory and antioxidative Morindolide on the crosstalk between MEK1/JNK/NF-kB/iNOS and Nrf2/HO-1 pathways / Assoc. Prof. Dr. Mizaton Hazizul Hasan ... [et al.] - Hasan, Mizaton Hazizul; Zakaria, Yuslina; Jahidin, Aisyah Hasyila; Amom, Zulkhairi; Mohd Hatta, Fazleen Haslinda; Elhassane, Anour (Faculty of Pharmacy, 2023)
Inflammation could cause chronic, life-threatening diseases, including arthritis, diabetes, cardiovascular diseases and even cancer that are the greatest threat to human health. It is reported that non-steroidal anti-inflammatory drugs (NSAIDs) are the most common anti-inflammatory and analgesic drugs responsible for 5 to 10 % of all prescribed medications, annually. However, NSAIDs are recommended with caution, and their use should be limited to the lowest effective dose and shortest duration. In addition, common gastrointestinal, renal and cardiovascular side effects should be monitored during the use of the drugs.